Eosinophilic Granulomatous Dermatitis Due to Hairy vetch (Vicia villosa Roth) Poisoning in a Holstein Cow - Eroksuz, Y; Polat, E; Akdeniz Incili, C; Karabulut, B; Sagliyan, A; Eroksuz, H (Journal of the Hellenic Veterinary Medical Society, 2023)
Eosinophilic granulomatous dermatitis is reported due to Hairy vetch (Vicia villosa Roth) consumption in a 3-year-old Holstein cow. Cow showed dermatitis over the face, neck and perineum in last 2-month of period. Biopsy samples were taken surgically by local anestesia. The lesions were characterized by multifocal eosinophilic granulomatous dermatitis. Immunohistochemistry demonstrated a marked and diffuse and immunostaining CD3, whereas CD20 and CD68 staining were not so prominent. The plant-lesion relationship was well-established. After the owner stopped feeding the vetch, skin lesions were regressed 6 months later and completely resolved 12 months.